2014
DOI: 10.1177/0148607113517266
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Oral Nutrition Supplementation Improves Outcomes in Malnourished Patients With Chronic Kidney Disease on Hemodialysis

Abstract: Background: There is no consensus on the type, time of initiation, or duration of use of enteral nutrition in patients with chronic kidney disease (CKD). This study aimed to compare the effects of a renal-specific oral nutrition supplement (RS-ONS) and a standard recommended nutrition regime on biochemical and nutrition markers in malnourished patients with CKD on hemodialysis. Methods: Sixty-two malnourished patients with CKD, divided into experimental (RS-ONS; n = 32; mean [SD] age, 62.0 [11.3] years; 55.2% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
0
11

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 21 publications
4
62
0
11
Order By: Relevance
“…3,13,14,16 As well as studies that examined the effects of food supplements on gastrointestinal symptoms during hemodialysis reported similar or even less nausea and vomiting incidences. 16,29,30 …”
Section: Discussionmentioning
confidence: 99%
“…3,13,14,16 As well as studies that examined the effects of food supplements on gastrointestinal symptoms during hemodialysis reported similar or even less nausea and vomiting incidences. 16,29,30 …”
Section: Discussionmentioning
confidence: 99%
“…A study performed by Bolasco et al showed that oral amino acid supplements increase the dialysis adequacy based on Kt/V in intervention groups, although no statistically significant difference was observed (17). Findings of a study conducted by Caesar et al (5) show no statistically significant difference based on URR in the intervention group in comparison to the control group, which may be because of the difference in sample size, daily diet in different cultures, intervention duration, and other factors influencing the dialysis adequacy (such as diet, individual’s size, training to patients, underlying diseases, filter type, dialysis duration, blood flow rate, dialysis flow rate, and urea distribution volume that in turn depend on the gender, height, and weight (24)). Given various studies and their results as well as the findings of the present study on the need to use protein-based oral nutritional supplements in dialysis patients and the prevalence of this issue, it is recommended to perform studies with larger sample size across a longer period of time.…”
Section: Discussionmentioning
confidence: 94%
“…Recently, protein-energy malnutrition (PEM) and systemic inflammation were found to be common in hemodialysis patients (1-4). Results of various studies show that daily intake of energy and protein in hemodialysis patients is less than the recommended dietary intake (energy: 35 kcal/kg/day and protein: 1 - 1.2 g/kg/day) (5-8). Unfortunately, 6% - 8% of hemodialysis patients suffer from severe malnutrition and 30% - 35% from moderate malnutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Finally it is important to remember that the relevance of the regular nutritional assessment in patients with CKD is not solely in recognizing the presence of a problem but also, or even primarily, in providing adequate nutritional support intended to alleviate the problem. There is ample evidence published in the literature that nutritional support of malnourished patients with CKD leads to an improvement of nutritional status parameters, lowering of markers of chronic inflammation, a better quality of life and decreased number of hospitalizations (16)(17)(18)(19)(20)(21). Our patients will be grateful for these outcomes, particularly the latter two.…”
Section: Introductionmentioning
confidence: 85%